Design, synthesis and molecular modeling of isatin-aminobenzoic acid hybrids as antibacterial and antibiofilm agents - Awwad A. Radwan; Fares K. Al-Anazi; Mohammed Al-Agamy; Adel F. Alghaith; Gamal M. Mahrous; Mohammad R. Alhuzani; Abdulrhman S.A. Alghamdi (Saudi Pharmaceutical Journal)
Number of factors, including newly emerging infectious diseases and an increase in multi-drug resistant microbial pathogens with particular relevance for Gram-positive bacteria, make the treatment of infectious diseases in hospital-based healthcare a major challenge in the medical community. 4-Aminobenzoic acid (PABA), has demonstrated a variety of biological actions particularly, antimicrobial activity. In our study we coupled this vitamin-like molecule with different isatin derivatives. We investigated the antibacterial activity of the synthesized Schiff's bases. The compounds showed high selective activity against Gram-positive bacteria and showed weak or no activity against both Gram-negative bacteria and fungi. Compound 2a showed highest activity against S. aureus and B. subtilis (MIC 0.09 mmol/L). Additionally, these substances exhibit strong anti-B. Subtilis biofilm formation. We were able to shed insight on the binding mode of these new inhibitors using in silico docking of the compounds in the binding sites of a 3D structure of B. subtilis histidine kinase/Walk. The binding free energy of the compound 2a to the catalytic domain walk, of histidine kinase enzyme of B. subtilis bacteria, was calculated using molecular mechanics/generalized born surface area scoring. The key residues for macromolecule–ligand binding were postulated. The optimized 3D protein–ligand binding modes shed light on the B. subtilis HK/Walk–ligand interactions that afford a means to assess binding affinity to design new HK/Walk inhibitor as antibacterial agents.